Pengembangan media pembelajaran kartu truth or dare islami sebagai upaya meningkatkan pemahaman pembelajaran agama - Jamilah, Tsania Nisaul; Fariq, M. Amir; Pramandyah, Nizam Ihludy (Maliki Interdisciplinary Journal, 2025)
Learning is actually an interactive communication that involves teachers and students and also their learning resources in a learning community. Every learning needs media as an introduction to quickly distribute information. But often this is ignored by teachers in their learning. This article aims to analyze the application of Truth or Dare media in Islamic Religious Education learning. This research method uses a qualitative method, namely by taking data sourced from observations, documentation, and interviews. The results of the study show that the application of Truth or Dare media is able to increase the activeness and participation of students in the learning process. This indicates that Truth or Dare media is effective in increasing understanding and also succeeds in creating a fun, fun, and interactive learning atmosphere that attracts students’ interest and motivation to learn.